Management of acral lentiginous melanoma: current updates and future directions - Dugan, Michelle M.; Perez, Matthew C.; Karapetyan, Lilit; Zager, Jonathan S. (Frontiers in Oncology, 2024)
Acral lentiginous melanoma is a rare subtype of melanoma generally associated with poor outcomes, even when diagnosed at an early stage. The tumor genetic profile remains poorly understood, but it is known to have a suppressed immune environment compared to that of nonacral cutaneous melanomas, which limits therapy options. There is significant attention on the development of novel therapeutic approaches, although studies are limited due to disease rarity.For local disease, wide local excision remains the standard of care. Due to frequent under-staging on preoperative biopsy, wider margins and routine sentinel lymph node biopsy may be considered if morbidity would not be increased.For advanced disease, anti-PD1 monotherapy or combination therapy with anti-PD1 and anti-CTLA4 agents have been used as first-line treatment modalities. Anti-PD1 and anti-CTLA4 combination therapies have been shown to be particularly beneficial for patients with BRAFmutant acral lentiginous melanoma. Other systemic combination regimens and targeted therapy options may be considered, although large studies with consistent results are lacking. Regional and intralesional therapies have shown promise for cutaneous melanomas, but studies generally have not reported results for specific histologic subtypes, especially for acral melanoma.Overall, the unique histologic and genetic characteristics of acral lentiginous melanoma make therapy options significantly more challenging. Furthermore, studies are limited, and data reporting has been inconsistent. However, more prospective studies are emerging, and alternative therapy pathways specific to acral lentiginous melanoma are being investigated. As further evidence is discovered, reliable treatment guidelines may be developed.